Bilateral thalamic infarction due to artery of Percheron occlusion: a case report - Shah, Maleeha; Nadeem, Muhammad Daniyal; Saleem, Ayesha; Khan, Muhammad Taimoor; Asghar, Neelam (Journal of the Pakistan Medical Association, 2022)
The artery of Percheron is a rare variant of the posterior cerebral circulation. It is characterised by a single arterial trunk that supplies blood to bilateral paramedian thalami and rostral midbrain. Its occlusion can have a very wide range of presentation, and initial imaging including CT of the head maybe normal. Diagnosis and eventual treatment is usually delayed. We describe the case of an elderly man who presented with loss of consciousness, aphasia, and bilateral lower limb weakness. He was diagnosed with bilateral thalamic infarction due to the occlusion of the artery of Percheron only after an MRI of the brain was performed. Despite treatment his symptoms did not resolve completely. Keywords: Thalamus/blood supply, Cerebral arteries, Magnetic Resonance Imaging.